The Role of Knowledge Creation, Sharing and Utilization to the Resource based View of Competitive Advantage (Global Journal of Management and Business Research, 2019)
Almost every organization strives to make a profit by offering to the market a single value that cannot be provided by competitors. This uniqueness is what gives an organization a competitive advantage over rival organizations, and help it to reach its objectives. Henceforth, to build such singularity over time supposes the possession of a knowledge that others have not. This paper discusses the extent to which knowledge creation, sharing, and utilization are crucial in creating competitive advantage. Therefore, this articleevolves around key factors that create and maintain competitive advantage; among them, we note mechanisms through which knowledge is acquired and developed, the role of management styles in knowledge management settings, the organization status, the innovation process, and the strategic management.
Keywords: competitive advantage; innovation; knowledge; knowledge management; leadership; learning organization; organizational learning; strategic management